A multi-component heavy oil recovery method
By using the coordinated injection of composite gas and steam and the injection of chemical additives in heavy oil reservoirs, the problems of inter-well flow, heat fluctuation, and invasion of water bodies at the edge of traditional steam injection thermal production technology are solved, and the problem of intrusion between wells is achieved. Efficient heavy oil production effect.
Patent Information
- Application Number
- CN202411699922.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Traditional steam injection and heat production technology has problems such as steam flow between wells, small steam heat wave range, low heat exchange efficiency, and invasion of water bodies at the edge of the bottom in low-permeability thick oil reservoirs, resulting in low production capacity and poor thermal production effect.
Using a multi-variable thermal composite development technology based on composite gas (carbon dioxide and nitrogen) + steam + chemical additives, the heat transfer speed is improved by mixing carbon dioxide and nitrogen with steam and then injecting chemical additives with appropriate conditions. , reduce crude oil viscosity and promote reservoir production.
This method effectively opens the high permeability channel, improves the heating range and action distance of steam, reduces the viscosity of heavy oil, improves the recovery rate of the reservoir, reduces the invasion of the edge bottom water, and improves the thermal recovery effect.
Smart Images

Figure CN119195713B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil and gas field development engineering, and in particular to a multi-component heavy oil production method. Background Art
[0002] Due to the high viscosity of crude oil under the original reservoir conditions (the viscosity of formation crude oil is greater than 50mPa·s or the viscosity of ground degassed crude oil is greater than 100mPa·s), it is difficult to effectively develop heavy oil reservoirs by relying solely on natural energy or cold recovery technologies such as water flooding and chemical flooding, and the production capacity is low. Therefore, effective viscosity reduction is the main problem faced by the development of heavy oil reservoirs. Steam injection thermal recovery has become the main development technology for heavy oil reservoirs at home and abroad, including steam stimulation, steam flooding and steam-assisted gravity drainage (SAGD). Among them, steam stimulation is the most widely used thermal recovery development method for heavy oil, with a stimulation recovery rate of 20%~35% and a gasoline ratio of 3.0~5.22. It is suitable for reservoirs with oil layer thickness exceeding 10m, burial depth below 900m, porosity above 0.3, and oil saturation above 0.4.
[0003] The traditional steam injection thermal recovery technology has the following problems when applied to low permeability heavy oil reservoirs:
[0004] (1) Steam crossflow between wells: The causes of steam crossflow include intra-layer or inter-layer heterogeneity, severe steam overburden in thick oil layers, unreasonable steam injection parameters, injected fluid tongue-in along the main flow line between injection and production wells, and continuous steam injection leading to thermal or pressure connection between wells.
[0005] (2) During the seepage process, the steam dryness decreases rapidly with the increase of the migration distance, so the steam heat has a small range and the heat exchange efficiency is low.
[0006] (3) Problem of water intrusion at the edge and bottom: Water intrusion at the edge and bottom is an important issue that affects the effect of thermal recovery of heavy oil. In the thermal recovery process of heavy oil reservoirs with water at the edge and bottom, the water cone or water ridge formed by water intrusion is the main factor leading to poor thermal recovery effect. The reasons include geological and engineering factors such as reservoir heterogeneity, poor cementing quality, perforation of water layers, improper thermal recovery improvement measures and unreasonable steam injection parameters. When the thermal recovery well is connected to the water layer, the average water content of the oil well rises sharply, affecting the normal production of the oil well.
[0007] At present, the conventional single steam injection method is no longer suitable for the efficient development of heavy oil reservoirs. Summary of the invention
[0008] The inventors have found that in order to solve the above problems, the present invention provides a multi-component heavy oil recovery method, in which a multi-component thermal composite development technology based on composite gas + steam + chemical additives is proposed. Carbon dioxide has high solubility in heavy oil, which helps to extract light components in heavy oil, but the single use of carbon dioxide for steam flooding is prone to serious steam channeling; nitrogen has poor solubility in heavy oil and a large expansion coefficient, which can expand the heating range of steam. To a certain extent, the injection of nitrogen can inhibit the channeling of edge and bottom water. The present invention forms a composite steam displacement by compounding carbon dioxide and nitrogen in a certain proportion, opens a high permeability channel, and does not cause serious steam channeling. Multi-component thermal fluid recovery technology is a composite thermal recovery technology that injects N2, CO2 gas and high-temperature steam into the oil reservoir at the same time to displace crude oil. The high temperature of water vapor can effectively reduce the viscosity of crude oil. The miscibility of CO2 and crude oil not only further reduces the viscosity of crude oil, but also the volume of crude oil can expand by 10%-40% after the crude oil dissolves CO2, which improves the flow state of crude oil; N2 has a large compression coefficient, and when injected at high pressure, the higher expansion energy can supplement the formation energy. During the injection of multi-component thermal fluids into the formation, the rapid seepage of gas in the multi-component thermal fluids accelerates the heat transfer rate, which can effectively overcome the heat loss along the steam drive. At the same time, the hot water formed by the steam after heat exchange with the formation fluid alleviates the formation of gas channeling to a certain extent. In addition, the addition of chemical additives can further reduce the viscosity of heavy oil and promote the flow of heavy oil. The pores generated after the heavy oil flows out provide high-permeability channels for subsequent nitrogen and carbon dioxide steam drives, thereby improving the recovery of heavy oil reservoirs.
[0009] The present invention provides a multi-component heavy oil production method, which comprises the following steps:
[0010] S1: Carbon dioxide and nitrogen are mixed with steam and injected into the injection well in the form of a mixed gas, wherein the molar fraction of carbon dioxide is 20%-30% and the molar fraction of nitrogen is 70%-80%.
[0011] S2: When the production oil-gas ratio is greater than 1000m 3 / t, the chemical additive slug injection stage is carried out, and the chemical additive slug is injected into the formation through the injection well; wherein the chemical additive injection amount is 0.5-1PV;
[0012] Wherein, the chemical auxiliary agent is a composite auxiliary agent modified by nanomaterials and water-soluble polymers; or the chemical auxiliary agent is a composite auxiliary agent modified by nanomaterials and oil-soluble polymers. Figure 1 As shown, Figure 1 A flow chart of the multi-component heavy oil recovery method of the present invention is shown.
[0013] Optionally, in step S1, the molar fraction of carbon dioxide is 24%-27%, and the molar fraction of nitrogen is 73%-76%. The present invention controls the ratio of carbon dioxide to nitrogen to prevent excessive carbon dioxide content from causing serious turbulence.
[0014] Optionally, the injection rate of the mixed gas is 1-2 mL / min. Generally speaking, when the injection rate of the mixed gas is too high, it will cause the steam to start to transfer heat to a long distance in time. The present invention can expand the expansion range of steam and the effective distance of steam within the injection rate range by mixing carbon dioxide and nitrogen in a certain ratio.
[0015] Optionally, in step S1, the mole fraction of carbon dioxide is 25%, and the mole fraction of nitrogen is 75%.
[0016] Optionally, the heavy oil is an oil reservoir with a burial depth of more than 1,800 meters, a permeability of less than 300 mD, and a crude oil viscosity of more than 200 mPa·s. Optionally, the crude oil viscosity is greater than 10,000 mPa·s.
[0017] Optionally, the water-soluble polymer is one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium 9,10-dihydroxystearate, sodium lauryl polyether sulfate, hexadecylaminobenzenesulfonic acid, and hexadecyltetramethylammonium bromide.
[0018] Optionally, the nanomaterial is one or more of ferroferric oxide, copper ferrite, nano-silicon dioxide, nano-titanium dioxide, nano-cellulose, nano-porous graphene, and carbon nanotubes.
[0019] Among them, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium 9,10-dihydroxystearate and sodium lauryl alcohol polyether sulfate are anionic emulsified viscosity reducers with good temperature resistance, but generally anionic emulsified viscosity reducers are very easy to precipitate with high-valent cations in the formation, resulting in reduced performance. Nanomaterials have the characteristics of small particle size (average particle size less than 100nm) and large specific surface area, and have good ability to adsorb heavy oil asphaltene, but nanomaterials are difficult to disperse in heavy oil systems. Modifying and compounding nanomaterials with anionic emulsified viscosity reducers can, to a certain extent, avoid the interaction between anionic emulsified viscosity reducers and cations in the formation, and at the same time make the nanomaterials evenly dispersed in the heavy oil system.
[0020] In addition, hexadecylaminobenzenesulfonic acid and hexadecyltetramethylammonium bromide are cationic emulsified viscosity reducers. Since most rocks are negatively charged, they have a strong adsorption effect on cationic emulsified viscosity reducers, which will lead to a decrease in their performance. The present invention, by modifying and compounding nanomaterials with cationic emulsified viscosity reducers, can, to a certain extent, avoid the reaction between the cationic emulsified viscosity reducers and anions in the formation.
[0021] Optionally, the mass ratio of the nanomaterial to the water-soluble polymer or the oil-soluble polymer is 0.3-1:1.
[0022] Optionally, the water-soluble polymer or oil-soluble polymer is a polymer formed by homopolymerization or copolymerization of at least three unsaturated monomers;
[0023] Wherein, the unsaturated monomer is maleic anhydride, stearic acid, styrene, vinyl acetate, acrylic acid, octadecyl acrylate, 4-vinylpyridine, acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt or nonionic polyether acrylate.
[0024] Optionally, the preparation method of copper ferrite comprises the following steps:
[0025] Fe 3+ Salt solution and Cu 2+ The salt solution is mixed, alkali is added to adjust the pH to 7-8, the reaction is carried out at a temperature of 90-105°C, and then after washing, drying and grinding, it is placed at 400°C-500°C for roasting to obtain the magnetic nano material copper ferrite.
[0026] Cu 2+ with Fe 3+ The molar ratio is 1:2-3.
[0027] Optionally, the base is sodium hydroxide or potassium hydroxide.
[0028] Optional, Fe 3+ The salt solution can be ferric nitrate or ferric chloride solution. 2+ The salt solution may be a solution of copper chloride, copper nitrate or copper sulfate.
[0029] Copper ferrite magnetic nanoparticles have high magnetism and are not easily oxidized and corroded. They are non-toxic and harmless and can be used as magnetic materials for viscosity reducers. The composite additives obtained by compounding the magnetic material with other nanomaterials and water-soluble or oil-soluble polymers can be recycled and reused after use.
[0030] Optionally, the preparation method of the composite auxiliary agent comprises the following steps:
[0031] (1) The nanomaterial is placed in anhydrous ethanol for ultrasonic dispersion, and then a coupling agent is added and the temperature is raised to 80-100°C, and the mixture is stirred vigorously. The mixture is then cooled to room temperature, centrifuged, washed, and dried to obtain a modified nanomaterial. The modified nanomaterial has improved compatibility.
[0032] (2) adding octadecyl acrylate, 4-vinylpyridine and acrylamide into a reaction vessel, adding toluene as a reaction solvent, and then adding the modified nanomaterial, adding an initiator dropwise at a temperature of 80-90°C, cooling to room temperature after the reaction is completed, using methanol to swell the reaction product, allowing the nanomaterial grafted copolymer to precipitate, and then washing and drying in sequence to obtain a composite auxiliary agent;
[0033] The molar ratio of octadecyl acrylate, 4-vinylpyridine and acrylamide is 4-5:2-3:1, and the added amount of the modified nanomaterial is 20%-30% of the total mass of the unsaturated monomers.
[0034] Furthermore, the composite additive prepared by the method is obtained by copolymerizing three monomers, namely, octadecyl acrylate, 4-vinyl pyridine and acrylamide, with modified nanomaterials. Octadecyl acrylate has a long-chain alkyl group, which can increase the oil solubility of the copolymer. 4-vinyl pyridine has an aromatic ring structure, which has good permeability to the aggregated system of colloids and asphaltene in the heavy oil. Moreover, the N atom on the pyridine ring can synergize with the strong polar amide group in acrylamide to destroy the hydrogen bond structure in the heavy oil. The oil solubility and steric hindrance of the grafted copolymer are utilized to improve the solubility and dispersibility of the nanomaterial in the heavy oil. At the same time, the adsorption performance of the nanomaterial and the penetration and disassembly effect of the oil-soluble polymer are brought into play, so as to achieve the synergistic viscosity reduction effect of the two.
[0035] Optionally, the preparation method of the composite auxiliary agent comprises the following steps:
[0036] (1) The nanomaterial is placed in anhydrous ethanol for ultrasonic dispersion, and then a coupling agent is added and the temperature is raised to 80-100°C, and the mixture is stirred vigorously. The temperature is then lowered to room temperature, and the mixture is centrifuged, washed, and dried to obtain a modified nanomaterial;
[0037] (2) Add acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and non-ionic polyether acrylate into a reaction container and add distilled water, cool to below 10°C, adjust the pH to 7-8, then add modified nanomaterials, add initiator to carry out polymerization reaction, then add alkali to carry out hydrolysis at a temperature of 70-80°C, dry in a fluidized bed, crush and screen to obtain a composite additive.
[0038] The molar ratio of acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and non-ionic polyether acrylate is 2-3:2-3:1-2:1, and the added amount of the modified nanomaterial is 10%-20% of the total mass of the unsaturated monomer.
[0039] Furthermore, the composite auxiliary agent prepared by this method introduces surface-active monomers, non-polar rigid monomers and modified nanomaterials into the main chain of acrylamide polymer for copolymerization. The obtained composite auxiliary agent has amphiphilicity, high molecular heat and salt resistance and high molecular efficiency. At the same time, the high-boundary surface active groups introduced into the main chain of the polymer molecule realize the high surface activity of the molecule and higher emulsification and viscosity reduction performance, while exerting the adsorption properties of the nanomaterials and the penetration and disassembly effect of the polymer to achieve the synergistic viscosity reduction effect of the two.
[0040] Optionally, the initiator is one or more of azobisisobutyronitrile, ammonium sulfate or sodium bisulfite.
[0041] Optionally, the coupling agent may be one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.
[0042] Compared with the prior art, the present invention achieves at least one of the following beneficial effects:
[0043] (1) The multi-component heavy oil recovery method of the present invention forms a composite steam drive by compounding carbon dioxide and nitrogen in a certain proportion, which opens a high permeability channel without causing serious bubbling. The addition of chemical additives can further reduce the viscosity of the heavy oil and promote the flow of the heavy oil. The pores generated after the heavy oil flows out provide a high permeability channel for subsequent nitrogen and carbon dioxide steam drive, thereby improving the recovery of the heavy oil reservoir.
[0044] (2) In the multi-component heavy oil recovery method of the present invention, three monomers, namely, octadecyl acrylate, 4-vinyl pyridine and acrylamide, are copolymerized with modified nanomaterials to obtain a composite auxiliary agent. Octadecyl acrylate has a long-chain alkyl group, which can increase the oil solubility of the copolymer. 4-vinyl pyridine has an aromatic ring structure and has good permeability to the aggregated system of colloids and asphaltene in the heavy oil. In addition, the N atom on the pyridine ring can synergistically act with the strong polar amide group in acrylamide to destroy the hydrogen bond structure in the heavy oil. The oil solubility and steric hindrance of the grafted copolymer are utilized to improve the solubility and dispersibility of the nanomaterial in the heavy oil. At the same time, the adsorption performance of the nanomaterial and the penetration and disassembly effect of the oil-soluble polymer are brought into play, so as to achieve the synergistic viscosity reduction effect of the two.
[0045] (3) In the multi-component heavy oil recovery method of the present invention, a surface-active monomer, a non-polar rigid monomer and a modified nano-material are introduced into the main chain of the acrylamide polymer for copolymerization, and the obtained composite additive has both high molecular weight heat and salt resistance and high molecular weight efficiency. At the same time, the high-boundary surface active groups introduced into the main chain of the polymer molecule realize high surface activity and high emulsification and viscosity reduction performance of the molecule, and at the same time, the adsorption performance of the nano-material and the penetration and disassembly effect of the polymer are brought into play, so as to achieve the synergistic viscosity reduction effect of the two. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0047] Figure 1 An exemplary embodiment of a flow chart of a multi-component heavy oil recovery method of the present invention is shown. DETAILED DESCRIPTION
[0048] In order to more clearly illustrate the overall concept of the present invention, a detailed description is given below in an exemplary manner in conjunction with the accompanying drawings.
[0049] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and therefore, the scope of protection of the present invention is not limited by the specific embodiments disclosed below. In the description of this specification, the description of reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily have to be directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0050] Example 1
[0051] The multi-component heavy oil recovery method comprises the following steps:
[0052] S1: Carbon dioxide and nitrogen are mixed with steam and injected into the injection well in the form of a mixed gas at a rate of 1 mL / min, wherein the mole fraction of carbon dioxide is 20% and the mole fraction of nitrogen is 80%.
[0053] S2: When the production oil-gas ratio is 1200m 3 / t, the chemical additive slug injection stage is carried out, and the chemical additive slug is injected into the formation through the injection well; wherein, the chemical additive injection volume is 0.5PV.
[0054] The chemical additive is a composite additive modified from nanomaterials and water-soluble polymers, and the mass ratio of the nanomaterials to the water-soluble polymers is 0.3:1.
[0055] The nano material is obtained by mixing ferroferric oxide, nano-titanium dioxide and nano-cellulose in a mass ratio of 1:1:1.
[0056] The water-soluble polymer is prepared by mixing sodium dodecyl sulfate, sodium lauryl polyether sulfate and hexadecyl aminobenzenesulfonic acid in a mass ratio of 1:2:1.
[0057] Example 2
[0058] The multi-component heavy oil recovery method comprises the following steps:
[0059] S1: After mixing carbon dioxide and nitrogen with steam, they are injected into the injection well in the form of mixed gas at a rate of 2 mL / min. The molar fraction of carbon dioxide is 30% and the molar fraction of nitrogen is 70%.
[0060] S2: When the production oil-gas ratio is 1200m 3 / t, the chemical additive slug injection stage is carried out, and the chemical additive slug is injected into the formation through the injection well; wherein the chemical additive injection volume is 1PV.
[0061] The chemical additive is a composite additive modified from nanomaterials and water-soluble polymers, and the mass ratio of the nanomaterials to the water-soluble polymers is 1:1.
[0062] The nano material is obtained by compounding copper ferrite, carbon nanotubes and nano cellulose in a mass ratio of 1:1:1.
[0063] The water-soluble polymer is prepared by mixing sodium dodecylbenzene sulfonate, sodium 9,10-dihydroxystearate and hexadecyltetramethylammonium bromide in a mass ratio of 1:1:1.
[0064] Example 3
[0065] The multi-component heavy oil recovery method comprises the following steps:
[0066] S1: After mixing carbon dioxide and nitrogen with steam, they are injected into the injection well in the form of mixed gas at a rate of 1.5 mL / min. The molar fraction of carbon dioxide is 25%, and the molar fraction of nitrogen is 75%.
[0067] S2: When the production oil-gas ratio is 1200m 3 / t, the chemical additive slug injection stage is carried out, and the chemical additive slug is injected into the formation through the injection well; wherein, the chemical additive injection volume is 0.8PV.
[0068] Among them, the chemical additive is a composite additive modified from nanomaterials and water-soluble polymers.
[0069] The preparation method of the composite auxiliary agent comprises the following steps:
[0070] (1) The nanomaterials nanocellulose and nanoporous graphene are ultrasonically dispersed in anhydrous ethanol at a mass ratio of 1:1, and then a silane coupling agent is added and the temperature is raised to 80°C. The mixture is stirred vigorously and then cooled to room temperature. The modified nanomaterials are obtained by centrifugation, washing and drying.
[0071] (2) adding octadecyl acrylate, 4-vinylpyridine and acrylamide into a reaction vessel, adding toluene as a reaction solvent, and then adding the modified nanomaterial, adding azobisisobutyronitrile as an initiator at a temperature of 80°C, cooling to room temperature after the reaction, using methanol to swell the reaction product, allowing the nanomaterial grafted copolymer to precipitate, and then washing and drying in sequence to obtain a composite auxiliary agent;
[0072] The molar ratio of octadecyl acrylate, 4-vinylpyridine and acrylamide is 4:2:1, and the added amount of the modified nanomaterial is 20% of the total mass of the unsaturated monomers.
[0073] Example 4
[0074] Based on Example 3, the main difference is that the preparation method of the composite auxiliary agent includes the following steps:
[0075] (1) The nanomaterials nanocellulose and nano titanium dioxide are ultrasonically dispersed in anhydrous ethanol at a mass ratio of 1:1, and then a silane coupling agent is added and the temperature is raised to 100°C. The mixture is stirred vigorously and then cooled to room temperature. The modified nanomaterial is obtained by centrifugation, washing and drying.
[0076] (2) adding octadecyl acrylate, 4-vinylpyridine and acrylamide into a reaction vessel, adding toluene as a reaction solvent, and then adding the modified nanomaterial, adding azobisisobutyronitrile as an initiator at a temperature of 90°C, cooling to room temperature after the reaction, using methanol to swell the reaction product, allowing the nanomaterial grafted copolymer to precipitate, and then washing and drying in sequence to obtain a composite auxiliary agent;
[0077] The molar ratio of octadecyl acrylate, 4-vinylpyridine and acrylamide is 5:2:1, and the added amount of the modified nanomaterial is 30% of the total mass of the unsaturated monomers.
[0078] Example 5
[0079] Based on Example 3, the main difference is that the preparation method of the composite auxiliary agent includes the following steps:
[0080] (1) placing nanomaterials copper ferrite and carbon nanotubes in anhydrous ethanol at a mass ratio of 1:1 and ultrasonically dispersing them, then adding a silane coupling agent and heating the mixture to 80°C, stirring the mixture vigorously, then cooling the mixture to room temperature, centrifuging, washing, and drying the mixture to obtain a modified nanomaterial;
[0081] (2) Add acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and nonionic polyether acrylate into a reaction container and add distilled water, cool to 8°C, adjust the pH to 7, then add modified nanomaterials, add initiators ammonium sulfate and sodium bisulfite to carry out polymerization reaction, then add alkali to hydrolyze at 70°C, dry in a fluidized bed, crush and screen to obtain a composite additive;
[0082] The molar ratio of acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and non-ionic polyether acrylate is 2:2:1:1, and the added amount of the modified nanomaterial is 10% of the total mass of the unsaturated monomers.
[0083] Example 6
[0084] Based on Example 3, the main difference is that the preparation method of the composite auxiliary agent includes the following steps:
[0085] (1) placing nanomaterials copper ferrite and carbon nanotubes in anhydrous ethanol at a mass ratio of 1:1 and ultrasonically dispersing them, then adding a silane coupling agent and heating the mixture to 100°C, stirring the mixture vigorously, then cooling the mixture to room temperature, centrifuging, washing, and drying the mixture to obtain a modified nanomaterial;
[0086] (2) Add acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and nonionic polyether acrylate into a reaction container and add distilled water, cool to 5°C, adjust the pH to 8, then add modified nanomaterials, add initiators ammonium sulfate and sodium bisulfite to carry out polymerization reaction, then add alkali to hydrolyze at 80°C, dry in a fluidized bed, crush and screen to obtain a composite additive;
[0087] The molar ratio of acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and non-ionic polyether acrylate is 3:2:2:1, and the added amount of the modified nanomaterial is 20% of the total mass of the unsaturated monomers.
[0088] Wherein, the preparation method of copper ferrite comprises the following steps:
[0089] The ferric chloride solution and the cupric chloride solution are mixed, and the pH is adjusted to 7 by adding sodium hydroxide, and the mixture is reacted at 90°C, and then washed, dried, and ground, and then calcined at 500°C to obtain the magnetic nanomaterial copper ferrite; wherein, Cu 2+ with Fe 3+ The molar ratio is 1:2.
[0090] Comparative Example 1
[0091] Based on Example 1, the main difference is that the molar fraction of carbon dioxide is 80%, and the molar fraction of nitrogen is 20%.
[0092] Comparative Example 2
[0093] Based on Example 1, the main difference is that the chemical additive contains only nanomaterials, and the nanomaterials are obtained by compounding ferroferric oxide, nano-titanium dioxide and nano-cellulose in a mass ratio of 1:1:1.
[0094] Comparative Example 3
[0095] Based on Example 1, the main difference is that the chemical auxiliary agent only contains water-soluble polymer sodium dodecyl sulfate.
[0096] Experimental example
[0097] The simulated heavy oil reservoir environmental conditions are: the reservoir permeability is 250mD; the reservoir burial depth is 2000m; the crude oil viscosity is 15000mPa·s; and the reservoir formation water salinity is 10000mg / L.
[0098] Test method:
[0099] Viscosity reduction rate determination: tested at 60°C according to method 6.4 in Q / SH10202193-2018.
[0100] Temperature resistance determination: Use a measuring cylinder to measure 60 mL of the prepared composite additive sample and pour it into a high-temperature and high-pressure heat treatment container. After sealing, place it in a constant temperature drying oven, bake it at 300°C for 24 hours, take it out, and after cooling, obtain a high-temperature treatment sample for use.
[0101] The performance tests of Examples 1-6 and Comparative Examples 1-3 are shown in Table 1.
[0102] Table 1 Performance test table
[0103]
[0104] Referring to Table 1, it can be seen that the multi-component heavy oil recovery method of the present invention, through the multi-component thermal composite development technology based on the composite gas + steam + chemical additive method, has an interfacial tension of less than 3.5×10 - 3 mN / m, and the viscosity reduction rate is over 97%, which can give full play to the displacement effect of multi-element thermal composite on heavy oil and improve the recovery rate of crude oil.
[0105] Compared with Example 1, although the viscosity reduction rate of Comparative Example 1 is not much different, in the simulated oil production process, steam channeling occurs too early in Comparative Example 1, resulting in a decrease in crude oil recovery.
[0106] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A multi-component heavy oil recovery method, characterized in that: The multi-component heavy oil recovery method comprises the following steps: S1: After mixing carbon dioxide and nitrogen with steam, they are injected into the injection well in the form of mixed gas, wherein the molar fraction of carbon dioxide is 20%-30% and the molar fraction of nitrogen is 70%-80%; S2: When the production oil-gas ratio is greater than 1000m 3 / t, the chemical additive slug injection stage is carried out, and the chemical additive slug is injected into the formation through the injection well; wherein the chemical additive injection amount is 0.5-1PV; Wherein, the chemical additive is a composite additive modified from a nano material and a water-soluble polymer; or the chemical additive is a composite additive modified from a nano material and an oil-soluble polymer; The nanomaterial is one or more of ferroferric oxide, copper ferrite, nano-silicon dioxide, nano-titanium dioxide, nano-cellulose, nano-porous graphene, and carbon nanotubes; The water-soluble polymer is one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium 9,10-dihydroxystearate, sodium laureth sulfate, hexadecylaminobenzenesulfonic acid, and hexadecyltetramethylammonium bromide; or the water-soluble polymer or the oil-soluble polymer is a polymer formed by homopolymerization or copolymerization of at least three unsaturated monomers.
2. The multicomponent heavy oil recovery method according to claim 1, characterized in that: In step S1, the molar fraction of carbon dioxide is 24%-27%, and the molar fraction of nitrogen is 73%-76%.
3. The multicomponent heavy oil recovery method according to claim 1, characterized in that: In step S1, the molar fraction of carbon dioxide is 25%, and the molar fraction of nitrogen is 75%.
4. The multicomponent heavy oil recovery method according to claim 1, characterized in that: Heavy oil refers to reservoirs with a burial depth of more than 1,800 meters, a permeability of less than 300 mD, and a crude oil viscosity greater than 200 mPa·s.
5. The multicomponent heavy oil recovery method according to claim 1, characterized in that: The mass ratio of the nanomaterial to the water-soluble polymer or the oil-soluble polymer is (0.3-1):
1.
6. The multicomponent heavy oil recovery method according to claim 1, characterized in that: The unsaturated monomer is maleic anhydride, stearic acid, styrene, vinyl acetate, acrylic acid, octadecyl acrylate, 4-vinylpyridine, acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt or nonionic polyether acrylate.
7. The multi-component heavy oil recovery method according to claim 1, wherein the preparation method of the copper ferrite comprises the following steps: Fe 3+ Salt solution and Cu 2+ The salt solution is mixed, alkali is added to adjust the pH to 7-8, the reaction is carried out at a temperature of 90-105°C, and then after washing, drying and grinding, it is placed at 400°C-500°C for roasting to obtain the magnetic nano material copper ferrite; Among them, Cu 2+ with Fe 3+ The molar ratio is 1:(2-3).
8. The multicomponent heavy oil recovery method according to claim 6, characterized in that: The preparation method of the composite auxiliary agent comprises the following steps: (1) The nanomaterial is placed in anhydrous ethanol for ultrasonic dispersion, and then a coupling agent is added and the temperature is raised to 80-100°C, and the mixture is stirred vigorously. The temperature is then lowered to room temperature, and the mixture is centrifuged, washed, and dried to obtain a modified nanomaterial; (2) adding octadecyl acrylate, 4-vinylpyridine and acrylamide into a reaction vessel, adding toluene as a reaction solvent, and then adding the modified nanomaterial, adding an initiator dropwise at a temperature of 80-90°C, cooling to room temperature after the reaction is completed, using methanol to swell the reaction product, allowing the nanomaterial grafted copolymer to precipitate, and then washing and drying in sequence to obtain a composite auxiliary agent; The molar ratio of octadecyl acrylate, 4-vinylpyridine and acrylamide is (4-5): (2-3): 1, and the added amount of the modified nanomaterial is 20%-30% of the total mass of the unsaturated monomers.
9. The multicomponent heavy oil recovery method according to claim 6, characterized in that: The preparation method of the composite auxiliary agent comprises the following steps: (1) The nanomaterial is placed in anhydrous ethanol for ultrasonic dispersion, and then a coupling agent is added and the temperature is raised to 80-100°C, and the mixture is stirred vigorously. The temperature is then lowered to room temperature, and the mixture is centrifuged, washed, and dried to obtain a modified nanomaterial; (2) Add acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and nonionic polyether acrylate into a reaction container and add distilled water, cool to below 10°C, adjust the pH to 7-8, then add modified nanomaterials, add initiator to carry out polymerization reaction, then add alkali to carry out hydrolysis at 70-80°C, dry in a fluidized bed, crush and screen to obtain a composite additive; The molar ratio of acrylamide, hydrophobic alkyl acrylamide, acrylamide alkyl ammonium chloride quaternary ammonium salt and non-ionic polyether acrylate is (2-3): (2-3): (1-2): 1, and the added amount of the modified nanomaterial is 10%-20% of the total mass of the unsaturated monomer.
10. The multi-component heavy oil recovery method according to claim 8 or 9, characterized in that: The initiator is one or more of azobisisobutyronitrile, ammonium sulfate or sodium bisulfite.
Citation Information
Patent Citations
Method for medium and low temperature controllable self heat generation under thick oil and ultra-thick oil deposit condition
CN103147732A
Method for controlling steam channeling of steam-injected oil reservoir
CN104314540A